Prediction of ICU Admission and its Outcome a Prospective Study of Different Scoring Systems in Women with Pregnancy Associated Sepsis - Rizwana Naz, Farukh Bashir, Zia Ullah, Navida Manzoor, Sadia Nisar, Nusrat Manzoor, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This study aims to compare the effectiveness of the Sequential Organ Failure Assessment (SOFA) and the Sepsis in Obstetrics Score (SOS) in predicting admission to intensive care and mortality in pregnant women with pregnancy-associated sepsis (PAS). Specifically, the researchers wanted to determine the performance of these two scoring systems. Methods: Cases were recruited from the obstetrics department who were diagnosed with PAS and met any two of the criteria for fast SOFA (qSOFA). At the time of admission, the features of SOFA and SOS were recorded and compared to determine the influence of these two models on patient outcomes. Place of Study: Hayat memorial teaching hospital Duration of Study: January 2021 to May 2022 Results: There were 30 intensive care patients, which leads to a significant fatality rate (31.7%). This was associated with the deaths of numerous patients. A criteria of SOFA less than 6 had the optimal combination of sensitivity (84.4%) and specificity (61,3%) for determining critical care admission for the study population. A cutoff value less than six produced the highest levels of sensitivity (64%) and specificity (40%) for the same. Conclusions: Compared to SOS, SOFA produced a significantly more accurate forecast of both the patient's dire health and the likelihood of their death. SOFA performed significantly better than SOS when assessing the proportion of PAS patients who required critical care hospitalization and the death rate. Keywords: SOFA · SOS · Obstetric sepsis ·